2017
DOI: 10.1021/acs.jpcc.7b11168
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation and Blinking of Single CsPbI3 Perovskite Quantum Dots

Abstract: We demonstrate using single molecule spectroscopy that inorganic CsPbI3 perovskite quantum dots (PQDs) undergo an irreversible, photoaccelerated reaction with water that results in a blue-shift of the photoluminescence (PL) and ultimately to complete quenching of the emission. We find that decomposition does not take place in the presence of oxygen alone but that it requires light and water. We also analyze the blinking for some stable PQDs and find a continuous distribution of emission states with a linear co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
173
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(195 citation statements)
references
References 65 publications
17
173
1
1
Order By: Relevance
“…Previous studies of lead halide perovskite NCs have observed photodegradation with an accompanying dynamical blueshift, attributed to a core-size reduction from surface destruction. 33,42 The measurements in this experiment were performed with a PMMA polymer encapsulation layer coated over the isolated CsPbBr 3 NCs, which is expected to act as a hydrophobic barrier and provide protection from water. 43 Thus, photodegradation at the highest intensities is expected to be caused by the opening of new, nonradiative sites as opposed to a waterassisted surface destruction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies of lead halide perovskite NCs have observed photodegradation with an accompanying dynamical blueshift, attributed to a core-size reduction from surface destruction. 33,42 The measurements in this experiment were performed with a PMMA polymer encapsulation layer coated over the isolated CsPbBr 3 NCs, which is expected to act as a hydrophobic barrier and provide protection from water. 43 Thus, photodegradation at the highest intensities is expected to be caused by the opening of new, nonradiative sites as opposed to a waterassisted surface destruction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…CsPbCl 3 and CsPbBr 3 nanocrystals are reported to be stable in the cubic phase, while CsPbI 3 slowly reverts to the thermodynamically-favored δ-phase, which is yellow. [54] For films in air, photobrightening followed by photodegradation was observed under illumination, and degradation is also observed for films in dark, ambient conditions. [59] Importantly, the δ phase for CsPbI 3 is nonluminescent, rendering the material unusable for most applications.…”
Section: Introductionmentioning
confidence: 95%
“…Yuan et al demonstrated that CsPbI 3 nanocrystals undergo irreversible photodegradation that quenches the photoluminescence under light irradiation. [54] For films in air, photobrightening followed by photodegradation was observed under illumination, and degradation is also observed for films in dark, ambient conditions. Additionally, several groups have been developing methods of protecting the perovskite structure from moisture, including overlaying silicone resins, [60] preparing polymer or related composites, [61][62][63] and coating with zwitterion [64] or metal complexes.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations